Una geografía para la guerra: narrativas del cerco en Francisco José de Caldas. - Felipe Martínez Pinzón. (Revista de Estudios Sociales, 2011)
In two emblematic texts–“Estado de la geografía del Virreinato de Santafé” (1807) and “Del influjo del clima sobre los seres organizados” (1808)–Francisco José de Caldas constructs a spatial narrative for the New Granada where the site of siege is localized at the center of the imagined map of the Vice-kingdom. The outside of civilization are the lowlands–and more radically, the jungle–with its mulatto, zambo, black, and indigenous populations, which always already threaten to take over the inside, the place of enunciation, a tempered climate of altitude, similar to that of Europe, inhabited by fantasized whites or light-skinned Hispanized/able mestizos. In creating a besieged geography, Caldas also invents a lasting paradigm whereby the Colombian state exercises warfare on its own territory as a means of actualizing its genetic narrative. Thus, this ideological construct sets in motion the menace of invasion as a ready-made dispositive that actualizes the polarities of Caldas’s exclusionary map.